Dr. Mumford - Kasdan, Lawrence; Core, Ericson; Dean, Loren; Davis, Hope; Lee, Jason (Buena Vista, 2004)
There are no earth-shaking payoffs here. No dramatic astonishments, vile betrayals or sexual surprises. Just the careful and loving creation of some characters it is mostly a pleasure to meet. And at its deepest level, profoundly down there below the surface, it is something more, I think: an expression of Kasdan's humanist longings, his wish that people would listen better and value one another more. It is the strangest thing, how this movie sneaks up and makes you feel a little better about yourself. [Roger Ebert, www.suntimes.com]
Keywords: DVD-Video